Produção e caracterização de filmes nanocelulósicos a partir de polpa de Acacia mearnsii de Wild. com diferentes teores de lignina residual - Gentil, Marina (2019)
The concern with the environment has been impelling researches about the elaboration of maintainable and biodegradable materials that reduce the impacts to the ecosystem. In the pulp and paper sector, nanotechnology emerges with this responsibility, adding value to the raw material at a nanometric scale and conferring excellent properties to the so-called nanocellulose and its derivatives. The use of unbleached cellulose pulp expands the use of the raw material and avoids the formation of chemical tailings formed in the bleaching stage. This work aimed to the production of gels for the formation of nanocellulosic films, evaluating the influence of residual lignin on the chemical, physical and mechanical properties of these films. Cellulose pulps of Acacia mearnsii were used with different kappa numbers: 0.5 (bleached sample); 11.5 and 16.7. The energy expenditure for the production of nanocellulosic gels was verified during different passes in the defibrillator mill. The gels were formed through mechanical defibrillation and characterized by zeta potential and viscosity, while the films were characterized by chemical, physical and mechanical tests. The samples differed in values with respect to the presence of lignin, where the energy spent for the production of the lower kappa gel was 0.324 kWh and for the highest kappa of 0.180 kWh. Regarding the tensile strength of these samples, the force required for the tear was 126.5 MPa and 74.9 MPa, respectively. The energy expenditure for the production of the gels differed statistically among the samples, making positive the presence of lignin. The increase in the number of passes in the mill influenced the formation of more homogeneous and resistant films. The presence of residual lignin did not confer significant antioxidant properties to the films and made them more susceptible to the trait.